2011
DOI: 10.4300/jgme-d-10-00178.1
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Resident-as-Teacher Curricula: A National Survey of Existing Programs and Future Needs

Abstract: Despite an Accreditation Council for Graduate Medical Education requirement for a RAT curriculum, some pediatrics programs still lack one, and some consider their program only moderately effective. A wealth of curricular material exists across programs, which could be shared nationally. Establishing a national RAT curriculum would offer programs resources to meet educational mandates and the ability to tailor programs to best fit their own program needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 9 publications
1
31
0
Order By: Relevance
“…In a recent study by Fromme et al, 4 87% of pediatrics training program directors reported they have a formal RAT curriculum, but half of programs allocate 10 hours or fewer for it during residency. In addition, only one-quarter of the responding program directors felt their RAT program was very effective.…”
Section: Introductionmentioning
confidence: 98%
“…In a recent study by Fromme et al, 4 87% of pediatrics training program directors reported they have a formal RAT curriculum, but half of programs allocate 10 hours or fewer for it during residency. In addition, only one-quarter of the responding program directors felt their RAT program was very effective.…”
Section: Introductionmentioning
confidence: 98%
“…Most existing resident-asteacher programs use lecture and workshops as the primary means of teaching residents to teach, which deprives the resident of the opportunity to practice and apply pedagogic skills. 23 Incorporating HPS into fellow teaching programs allows participants to have a more meaningful teaching experience by giving them the chance to apply and reinforce newly acquired skills and knowledge. Our study had similarities with that of Morrison and colleagues, 18 T which incorporated similar active learning techniques with multiple role-modeling sessions and assessed learners with an observed structured teaching encounter.…”
Section: Discussionmentioning
confidence: 99%
“…Several academic medical centers have attempted to address gaps in the graduate medical education (GME) curriculum and individual needs with institution-wide offerings. [1][2][3][4][5][6][7][8] However, many of these include only 1 content area.…”
Section: Introductionmentioning
confidence: 99%